A Dimension of Biophilia in Urban Design. Issue 1 (January 2020) - Amat, R C; Ismail, S; Wahab, M H; Ahmad, N H; Rani, W N M W M
Abstract: Erich Fromm coined the terminology of Biophilia in his book The Heart of Man. Hence, the concept was interpreted and established by Edward O. Wilson. It was described as human passionate of life and promoting well-being through natural elements. Throughout the years, the researchers show shreds of evidence of the positive benefits of nature interaction into human's life towards sustainable built environments. Biophilic is the terminology concept of design by integrating nature and natural elements, materials, and form in the built environment. The underpinnings theoretical frameworks are human experiences and the need for nature (Biophilia) through design principles and approaches (biophilic design) in the city built environment (urban design). This review paper will focus on the concept of Biophilia and biophilic by these two scholars, including Stephen Kellert and Elizabeth Calabrese that search through upon creating sustainable cities and restorative environment. The results will indicate the empirical evidence and call for further research on Biophilia in urban design.